(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In production, various sorbents are used to soften industrial waters, including sodium permutite, which removes calcium and magnesium ions from industrial waters, replacing them in an equivalent amount with sodium ions. At the same time, the water softens, but its mineralization remains, only cations are replaced. Permutite-softened waters are used in steam boilers, if in this case hydrogen permutite is used, the salinity decreases and the operation of steam boilers, especially high-pressure steam boilers, sharply improves, and their efficiency also increases markedly. The purpose of this study is to obtain hydrogen permutite and study its sorption properties. It has been established that hydrogen permutite can be obtained from aluminum trichloride and sodium silicate in an aqueous medium, while the accuracy of the component ratio plays an important role for the formation of hydrogen permutite.